Immunogenicity in Mamu-A*01 rhesus macaques of a CCR5-tropic human immunodeficiency virus type 1 envelope from the primary isolate (Bx08) after synthetic DNA prime and recombinant adenovirus 5 boost. - Vinner, L; Wee, E; Patel, S; Corbet, S; Gao, G; Nielsen, C; Wilson, J; Ertl, H; Hanke, T; Fomsgaard, A (2003)
Envelopes of primary R5-tropic human immunodeficiency virus type 1 (HIV-1) isolates may be particularly relevant for vaccine purposes and should be evaluated for immunogenicity in animals including macaques before carrying out human vaccine trials. In the present study, the immunogenicities of synthetic HIV-1 env DNA vaccines, which had been derived from the early primary isolate Bx08 and contain humanized codons, were evaluated in mice, guinea pigs and rhesus macaques. Neutralization sensitivity of the HIV-1(Bx08) isolate was found to resemble that of other primary isolate prototypes. Immunogenicity of gp120 delivered as codon-optimized DNA vaccine was comparable to that of recombinant gp120 protein plus adjuvant in mice. Similarly, DNA vaccination of guinea pigs with synthetic gp140(Bx08) and gp150(Bx08) DNA induced a strong antibody response independent of the gene construct and DNA immunization route. Mamu-A*01 rhesus macaques were DNA vaccinated with synthetic gp150(Bx08) or gp140(Bx08) DNA and boosted with a replication-deficient recombinant human adenovirus type 5 expressing a synthetic gp120(Bx08) gene. DNA-vaccinated rhesus macaques developed specific CD8+ T lymphocyte responses and anti-rgp120(IIIb) antibody responses. Both the humoral and cellular responses were significantly improved following intramuscular boosting with the recombinant adenovirus. The demonstrated humoral and cellular immunogenicities of these HIV Bx08 Env vaccines in non-human primates encourages their further development as one component in candidate HIV vaccines for humans.